Relative abundance and activity patterns of mesomammals in central Andes - Viscarra, Maria Estela; Ayala, Guido Marcos; Ticona, Herminio; Wallace, Robert Benedict (THERYA, 2022)
The natural history and ecology of mammals in the High Andes and Andean cloud forests are poorly known. This work aims to analyze the relative abundance and activity patterns of medium and large-sized mammals in the Andean portions of the Greater Madidi-Tambopata landscape using the camera trap methodology. Between 2012 to 2017, twelve sites were sampled covering an altitudinal gradient from 1,057 to 4,902 masl. A total of 311 digital camera trap stations were installed, and we applied a total effort of 5,144 trap nights (TN). We recorded a total of 21,346 photographs and 1,152 independent events from which we identified 28 species of mammals. The species with the highest relative abundance were Lycalopex culpaeus from 1 to 19.89/100TN, Didelphis pernigra from 0.1 to 10.71/100TN, and Eira barbara from 0.2 to 10.48/100TN. An analysis of activity patterns of the species that presented more than 10 independent events was carried out. The species with clearly nocturnal habits were Conepatus chinga, Cuniculus paca, Cuniculus taczanowskii, Didelphis pernigra, Mazama chunyi, Mazama americana, Dasypus novemcinctus, Didelphis marsupialis, Lagidium viscacia, Lycalopex culpaeus and Leopardus tigrinus, while Dasyprocta variegata, Nasua sp., Eira barbara, Hippocamelus antisensis and Tremarctos ornatus were diurnal; Puma concolor and Neogale mustela were cathemeral. The information obtained in our study responds to information gaps of a poorly studied mammal community and highlights the importance of Andean habitats for the conservation and management of montane species.